STYLISTICS IN “ASAHAN DALAM ANGKA 2015” TRANSLATION TEXT - Ely Ezir Marpaung; Syahron Lubis; Amrin Saragih; Eddy Setia (Universitas Islam Sumatera Utara (UISU), 2018)
This research deals with the role of stylistics in translation and is aimed at identifying the types of stylistics used in “Asahan Dalam Angka 2015” in the translation text, to analyze the application of how and why stylistics is applied. This study applies qualitative research method, proposed by Miles and Huberman. There are six types of stylistics applied in ASDA 2015translation text: Word Formation Variation (WFV), Lexical Choice Variation (LCV), Syntactical Order Variation (SOV), Semantic Meaning Variation (SMV), Pragmatic Contextual Variation (PCV), and Grammatical Change Variation (GCV). The application refers to the morphological process (Word Formation Variation).The words are lexically chosen to vary lexical meaning (LCV), the phrases are syntactically reconstructed SOV), the words are pragmatically and contextually varied and translated to be equivalent (PCV), and the words are grammatically changed and varied to construct appropriate meaning. The finding shows that there are two causes why stylistics is not well applied in ASDA 2015translation text. Firstly, MT (Machine Translation) used in translating the text is not equipped by sufficient linguistic devices. Secondly, ASDA 2015 translation text is not realized in stylistic variation.